A model experiment to understand the oral phase of swallowing of Newtonian liquids. Issue 14 (5th November 2015) - Hayoun, P.; Engmann, J.; Mowlavi, S.; Le Reverend, B.; Burbidge, A.; Ramaioli, M.
Abstract: A model experiment to understand the oral phase of swallowing is presented and used to explain some of the mechanisms controlling the swallowing of Newtonian liquids. The extent to which the flow is slowed down by increasing the viscosity of the liquid or the volume is quantitatively studied. The effect of the force used to swallow and of the gap between the palate and the roller used to represent the contracted tongue are also quantified. The residual mass of liquid left after the model swallow rises strongly when increasing the gap and is independent of bolus volume and applied force. An excessively high viscosity results in higher residues, besides succeeding in slowing down the bolus flow. A realistic theory is developed and used to interpret the experimental observations, highlighting the existence of an initial transient regime, at constant acceleration, that can be followed by a steady viscous regime, at constant velocity. The effect of the liquid viscosity on the total oral transit time is lower when the constant acceleration regime dominates bolus flow. Our theory suggests also that tongue inertia is the cause of the higher pressure observed at the back of the tongue in previous studies. The approach presented in this study paves the way toward a mechanical model of human swallowing that would facilitate the design of novel, physically sound, dysphagia treatments and their preliminary screening before in vivo evaluations and clinical trials.